Is Organization Theory Obvious to Practitioners? A Test of One Established Theory - Priem, Richard L.; Rosenstein, Joseph (Organization Science, 2000)
Critics have argued that organization theories which “work” are obvious to practitioners; that is, the theories simply confirm relationships that are already well understood by experienced managers. In our study, four types of respondents—Chief Executive Officers (CEOs) with business school education, CEOs without such education, graduating MBA students, and liberal arts graduate students—were presented with theory-based performance-rating tasks. These tasks identified respondents' beliefs regarding high-performance alignments of businesslevel strategy, structure, and environment for manufacturing firms. The respondents' cause maps were then compared to one another and to the alignment-performance relationships prescribed by business-level contingency theory. The graduating MBAs' cause maps reflected contingency theory most closely. The MBAs' cause maps were much closer to prescriptions of the theory, however, than were those of either the liberal arts graduate students or the experienced CEOs. This suggests that business-level contingency theory is not obvious to educated laypersons, or to highly experienced practitioners; both groups would find that the theory disconfirms aspects of their causal expectations. Further, each of the four respondent types in our study emphasized different contingency factors during the decision-making exercise. We discuss these results and their implications.